Matime law - Ostoja, Alfredo (1978)
The purpose of this paper is to analyze the legal nature of the time charter contract, as well as to determine the obligations of the parties involved in such contract, in the context of the appeal filed by Naviera Humboldt S.A. at the Tax Court against several resolutions. For this purpose, the different contracts of carriage are examined, which will make it possible to establish the legal nature of the time charter party contract and its differentiation from other kinds of contracts of carriage. This analysis will highlight the parties involved and the various functions they must perform as part of their contractual obligations. Finally, it will be concluded by delimiting the performances to be performed by each party to the contract and determining the most appropriate definition of time chartering.